2017
DOI: 10.1149/2.0441708jes
|View full text |Cite
|
Sign up to set email alerts
|

Activity Measurements of Gadolinium(III) Chloride in Molten LiCl-KCl Eutectic Salt Using Saturated Gd/GdCl3Reference Electrode

Abstract: The activity coefficients of rare earth chlorides in molten salt systems are of great interest for the research, development and commercialization of pyrochemical processing of spent nuclear fuels. In this paper, the activity coefficient of GdCl 3 in molten LiCl-KCl eutectic salt has been studied using a two electrode electrochemical cell with a gadolinium metal rod as working electrode and a saturated Gd|GdCl 3 -LiCl-KCl reference electrode. Use of this analyte reference electrode allows for the elimination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Bagri and Simpson, in a recent study, summarized the reported activity coefficient of GdCl 3 salt in LiCl-KCl salts, and compared their results using a Gd metal electrode and a reference electrode with Gd metal in a GdCl 3 -saturated LiCl-KCl salt. 9 To calculate the formal potential and activity coefficient of GdCl 3 , its Gibbs free energy of formation must be known, and it is needed to convert the Gd metal electrode potential vs the Ag/AgCl RE to a potential vs the Cl 2 /Cl − RE. For convenience, the potential difference of Ag/AgCl RE with respect to a Cl 2 /Cl − electrode from a recent study by Yoon et al 15 was used here.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bagri and Simpson, in a recent study, summarized the reported activity coefficient of GdCl 3 salt in LiCl-KCl salts, and compared their results using a Gd metal electrode and a reference electrode with Gd metal in a GdCl 3 -saturated LiCl-KCl salt. 9 To calculate the formal potential and activity coefficient of GdCl 3 , its Gibbs free energy of formation must be known, and it is needed to convert the Gd metal electrode potential vs the Ag/AgCl RE to a potential vs the Cl 2 /Cl − RE. For convenience, the potential difference of Ag/AgCl RE with respect to a Cl 2 /Cl − electrode from a recent study by Yoon et al 15 was used here.…”
Section: Resultsmentioning
confidence: 99%
“…Potentiometry is a well-established method for analyzing both aqueous and molten salt electrolytes. [7][8][9][10] It is based on the measurement of open circuit potentials (OCPs), also known as electromotive force (EMF) potentials, of an electrochemical cell. The OCP is dependent on temperature and the chemical activities of the species involved in the two half-cell reactions that comprise the overall cell reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As presented elsewhere in this report, equilibrium potentials were measured for LaCl3/La, CeCl3/Ce, NdCl3/Nd, and GdCl3/Gd in eutectic LiCl-KCl. The measured equilibrium potentials of the metals relative to a reference electrode were used to calculate apparent potentials (E * ) versus a standard Cl -/Cl2 potential, activity, and activity coefficient at concentrations ranging up to 4 mol % in eutectic LiCl-KCl [79,80]. The data indicated that the equilibrium potentials were more negative than those of the actinide chlorides over a wide range of rare earth chloride concentrations.…”
Section: Galvanic Drawdown Of Actinidesmentioning
confidence: 99%
“…12 Recently, Bagri et al published a series of papers on the measurement of equilibrium potentials for a select set of rare Earth metals (La, Ce, and Gd) in molten LiCl-KCl as a function of the rare Earth chloride concentration. [13][14][15] They used the EMF method with each rare Earth metal used as the working electrode. In the cases of CeCl 3 and GdCl 3 activity measurement, special reference electrodes were fabricated consisting of Ce/CeCl 3 and Gd/GdCl 3 .…”
mentioning
confidence: 99%